Hubungan Efikasi Diri Dengan Penyesuaian Akademik Pada Mahasiswa Fakultas Psikologi Angkatan 2021 Universitas Medan Area - Rahmadani, Annisa; Permatasari, Dinda (Universitas Medan Area, 2024)
This study aims to determine the correlation between self-efficacy and academic adjustment in students of the class of 2021 at the University of Medan. The scale used in this study is the self-efficacy scale and the adjustment scale where the subjects in this study are students from the 2021 University of Medan who conducted 97 students. The data analysis method used in this study is Product Moment correlation, so the following results can be obtained: there is a significant positive relationship between self-efficacy and academic adjustment. This result is evidenced by the correlation coefficient r = 0.783; P = 0.00 0.05, that self-efficacy contributes to academic adjustment by 61.3%. Students have high self-efficacy with empirical = 96.66 hypothetical mean = 75 where the second difference exceeds the SD number = 10,839 and student academic adjustment is high with empirical = 178.62 hypothetical mean = 137.5 where the difference between the two means exceeds the number SD = 16,312. From the results of this study, the proposed hypothesis is accepted.